2014 IEEE International Conference on Bioinformatics and Bioengineering 2014
DOI: 10.1109/bibe.2014.50
|View full text |Cite
|
Sign up to set email alerts
|

Toward Genomic Based Personalized Mathematical Models for Breast Cancer Tumor Growth

Abstract: Our Genomic Relevance Parameterization (GReP) model aims to explore a possible relationship between gene expression values from breast cancer patients and mathematical tumor growth modeling parameters calculated using data from clinical and preclinical measurements. We introduce two methods to relate genomic information and the tumor growth measurements. One method explores the impact of exponentiation of gene expression values, whereas the other utilizes the correlation between co-regulated genes and the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…We build artificial intelligence based mathematical models to compute tumor growth and related parameters including exponential-linear model parameters. In our earlier research [4], we have studied the relationship between the genetic information from breast cancer patients and the growth parameters, based on the genetic data retrieved from 79 breast cancer patients with ER+ status Modeling Tumor Growth for Kidney Cancer Based on Nuclei Clusters of Pathology Slides provided in I-SPY 1 TRIAL database [12]. Using the expression values of 74 breast cancer related genes from these patients and the tumor volume measurements obtained from NBIA database [13] as inputs to our computational models, we have computed tumor growth parameters.…”
Section: Modeling Tumor Growthmentioning
confidence: 91%
See 1 more Smart Citation
“…We build artificial intelligence based mathematical models to compute tumor growth and related parameters including exponential-linear model parameters. In our earlier research [4], we have studied the relationship between the genetic information from breast cancer patients and the growth parameters, based on the genetic data retrieved from 79 breast cancer patients with ER+ status Modeling Tumor Growth for Kidney Cancer Based on Nuclei Clusters of Pathology Slides provided in I-SPY 1 TRIAL database [12]. Using the expression values of 74 breast cancer related genes from these patients and the tumor volume measurements obtained from NBIA database [13] as inputs to our computational models, we have computed tumor growth parameters.…”
Section: Modeling Tumor Growthmentioning
confidence: 91%
“…In exponential-linear model, tumor growth is expressed as a function of rate constants and tumor weight or volume when no drug is administered [1]. In our previous work [4], we computed tumor growth curves using genetic information from breast cancer patients in our artificial intelligence based methods. In this paper, we study the generation of tumor growth models based on stained tissue samples of pathology slides from kidney cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier phase of our research (Saribudak et al 2014), we used 74 breast cancer-related genes which are reported as being significantly expressed in breast tissues (van't Veer et al 2002;Minn et al 2005;Ma et al 2009). van't Veer et al (2002) identified 70 prognostic marker genes to analyze their significance of expressions quantitatively in tumorous breast tissues.…”
Section: Gene Expression-based Parameter Calculationmentioning
confidence: 99%
“…For the 74 breast cancer-related genes reported as significant in literature (van't Veer et al 2002;Ma et al 2009;Minn et al 2005), we retrieved the gene expressions from I-SPY 1 TRIAL database (Edgar et al 2002) for 149 breast cancer patients. In this article, based on the promising results we obtained for tumor growth in Saribudak et al (2014), we extend our model with the inclusion of tumor shrinkage component of the mathematical model. Here, we present Personalized Relevance Parametrization (PReP-G) model which is capable of computing the tumor shrinkage behavior for a given set of chemotherapy regimens administered to xenograft models.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation